Menakar Direct Marketing dan Kepercayaan Pelanggan Dalam Pembelian Paket Umrah - Adi Suparwo; Mutiara Tristyantie (Jurnal Manajemen dan Bisnis, 2020)
This research aims to examine the implications of direct marketing and customer trust in the decision to purchase Umrah package at PT. Sanabil Madinah Barakah Bandung. This is supported by the rapid growth of tour and travel Umrah in some areas because of the needs of people who are mainly Muslims. The method used in this study is a verifiable, descriptive verificative using multiple linear regression where the free variables in this research are direct marketing and the trust of the customers and their current variables are purchase decisions. The sample techniques used in this research use nonprobability sampling techniques, namely purposive sampling techniques with samples obtained is a total of 92 respondents from a population of 1135 people. Simultaneous research resulted in the fact that direct marketing and customer trust jointly implicates the decision to purchase Umrah package at PT. Sanabil Madinah Barakah Bandung. This research shows that companies need to improve their direct marketing and customer trust in order to increase consumer buying decisions. Referring to this research, obtained by another invention of the variable that implicates the purchase decision seen from the greater coefficient of determinant is the trust of the customer, the better the company's control over employee service, facilities provided, and the guarantee of security to the customer, so it can also affect the customer's trust condition to the company that can ultimately increase the purchasing decision of the company.